2012
DOI: 10.1371/journal.pone.0044568
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Multiple Viral Infections Identified in Upper Respiratory Tract Infected Children under Three Years of Age in Shanghai, China

Abstract: BackgroundUpper respiratory tract infection (URTI) is a major reason for hospitalization in childhood. More than 80% of URTIs are viral. Etiological diagnosis of URTIs is important to make correct clinical decisions on treatment methods. However, data for viral spectrum of URTIs are very limited in Shanghai children.MethodsNasopharyngeal swabs were collected from a group of 164 children aged below 3 years who were hospitalized due to acute respiratory infection from May 2009 to July 2010 in Shanghai. A VRDAL m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 20 publications
12
60
2
1
Order By: Relevance
“…In conclusion, based on the present findings, there is no difference between the outcomes of a single adenovirus infection and co-infection with other mentioned 4 Arch Pediatr Infect Dis. 2017; 5(1):e36953.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In conclusion, based on the present findings, there is no difference between the outcomes of a single adenovirus infection and co-infection with other mentioned 4 Arch Pediatr Infect Dis. 2017; 5(1):e36953.…”
Section: Discussionsupporting
confidence: 53%
“…Co-infection with two or more viruses cannot be distinguished on the basis of clinical presentation (4). In such cases, the treatment goal should be management and control of all the co-infective agents (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infection has been reported to be common in children with an RTI. 3,20,30 RSV and MP were also found commonly in children with an RTI. 1.…”
Section: Discussionmentioning
confidence: 95%
“…63 Despite coinfection rates as high as 30%, the significance of these infections remains Integration of Technology Into Clinical Practice unclear. 63,64 The US Acute Gastroenteritis Etiology Study Team recently surveyed the cause of acute gastroenteritis in adults and found that nearly 10% of patients had mixed infections, many of which were mixed viral/bacterial infections. 65 Third, a high percentage of stool cultures submitted for diagnostic testing are not accompanied by orders for viral pathogens.…”
Section: Assessing Multiplex Panels and Their Possible Impact On The mentioning
confidence: 99%